Um estudo sobre a interação estrela-planeta a partirda relação massa-período planetário com a atividade estelar - Cavalcante, Francisco Jânio (2012)
In this work, we analyze the behavior of the chromospheric and coronal activities as a function of the mass and the orbital period of extrasolar planets which were detected by transit technique. So we look for possible effects of the planet on the star s chromosphere and corona. For this study we selected a sample of 48 stars with chromospheric activity indicator and 23 with coronal activity indicator. Our work is based on the work from Pont et al. (2011) in order to study stars with planets which were obtained by transit technique. Furthermore, we studied the relationship between planetary mass and orbital period with the chromospheric and coronal activity in order to better understand which influences the planets cause in the outer layers of stellar atmosphere. In our analysis we can observe that the mass of the planets exerts no influence in the stellar activity. However, we observed that the stellar coronal and chromospheric activities decrease with the increase of the orbital period of the planet